Pembiasaan Kegiatan Keagamaan di Madrasah Ibtidaiyah untuk Membentuk Karakter Religius Siswa Perspektif Empirisme - Maulidya, Difa; Cahyadi, Ani (el Buhuth: Borneo Journal of Islamic Studies, 2023)
This study aims to describe the habituation of religious activities to shape the religious character of students in ibtidaiyah madrasahs based on the perspective of empiricist philosophy. This research uses a descriptive qualitative approach. Data collection techniques in this study are interviews, observations, and documentation. The data analysis technique in this study uses the miles and huberman model which is divided into three activities in data analysis, namely data reduction, data presentation, and data verification. the philosophy of empiricism states that the environment greatly influences the formation of character and knowledge. The religious activities carried out will be experience and knowledge. Experience or knowledge that is carried out repeatedly will be a habituation that is expected to continue to be applied not only in the secluded but also in the home or community.